Possibility of SARS-CoV-2 Infection in the Metastatic Microenvironment of Cancer - Takuma Hayashi; Kenji Sano; Ikuo Konishi (Current Issues in Molecular Biology, 2022)
According to a report from the World Health Organization (WHO), the mortality and disease severity induced by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are significantly higher in cancer patients than those of individuals with no known condition. Common and cancer-specific risk factors might be involved in the mortality and severity rates observed in the coronavirus disease 2019 (COVID-19). Similarly, various factors might contribute to the aggravation of COVID-19 in patients with cancer. However, the factors involved in the aggravation of COVID-19 in cancer patients have not been fully investigated so far. The formation of metastases in other organs is common in cancer patients. Therefore, the present study investigated the association between lung metastatic lesion formation and SARS-CoV-2 infectivity. In the pulmonary micrometastatic niche of patients with ovarian cancer, alveolar epithelial stem-like cells were found adjacent to ovarian cancer. Moreover, angiotensin-converting enzyme 2, a host-side receptor for SARS-CoV-2, was expressed in these alveolar epithelial stem-like cells. Furthermore, the spike glycoprotein receptor-binding domain (RBD) of SARS-CoV-2 was bound to alveolar epithelial stem-like cells. Altogether, these data suggested that patients with cancer and pulmonary micrometastases are more susceptible to SARS-CoV-2. The prevention of de novo niche formation in metastatic diseases might constitute a new strategy for the clinical treatment of COVID-19 for patients with cancer.